Visiting Family and Friends in Southern California - Watkins, Howard::::::::: (1978)
Albert Watkins, Miriam doll, Adam Watkins wearing Indian headdress, Christine Watkins, Howard Watkins, Rose Watkins Front of Howard Arms Apartments at 4315 Burns Ave,, LA.